Resenha: CHEMISTRY — THE SCIENCE IN CONTEXT - Laroca, Sebastião (Acta Biológica Paranaense, 2009)
Resenha do livro: The book's name is Chemistry, the Science in Context (Second edition), the authors are Gilbert, Kirss, Foster and Davies, it was published in November 2009, by W. W. Norton & Company, inc., 500 Fifth Avenue, New York, NY 10110 <www.wwnorton.com>.